Determination of Financial Literacy and Financial Inclusion on MSME Performance and Sustainability - Nugroho, Febriawan Ardi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article draws on the findings of previous studies to determine the effects of financial inclusion and financial literacy on the viability and performance of micro, small, and medium-sized enterprises (MSME). Twenty articles from national and international journals from 2020–2023 were used to compile this Systematic Literature Review (SLR). Where research shows that: Financial Inclusion affects MSMEs' performance; Financial Inclusion affects MSMEs' sustainability; Financial Literacy affects Financial Inclusion of MSMEs; and Financial Literacy affects Financial Inclusion of MSMEs.